Extracellular Protons Mediate Presynaptic Homeostatic Potentiation at the Mouse Neuromuscular Junction. (15th July 2021) - Zhu, Yiyang; Warrenfelt, Claire I.C.; Flannery, Jill C.; Lindgren, Clark A.
Graphical abstract: Highlights: The retrograde mediator of presynaptic homeostatic potentiation (PHP) is unknown. We propose that protons signal PHP at the mouse neuromuscular junction (NMJ). Highly specific inhibitors of acid sensing ion channels (ASICs) prevent PHP. A slight (0.2 unit) decrease in extracellular pH mimics PHP via activation of ASICs. ASIC1 and 2a subunits are present at the mouse NMJ. Abstract: At the vertebrate neuromuscular junction (NMJ), presynaptic homeostatic potentiation (PHP) refers to the upregulation of neurotransmitter release via an increase in quantal content (QC) when the postsynaptic nicotinic acetylcholine receptors (nAChRs) are partially blocked. The mechanism of PHP has not been completely worked out. In particular, the identity of the presumed retrograde signal is still a mystery. We investigated the role of acid-sensing ion channels (ASICs) and extracellular protons in mediating PHP at the mouse NMJ. We found that blocking AISCs using benzamil, psalmotoxin-1 (PcTx1), or mambalgin-3 (Mamb3) prevented PHP. Likewise, extracellular acidification from pH 7.4 to 7.2 triggered a significant, reversable increase in QC and this increase could be prevented by PcTx1. Interestingly, an acidic saline (pH 7.2) also precluded the subsequent induction of PHP. Using immunofluorescence we observed ASIC2a and ASIC1 subunits at the NMJ. Our results indicate that protons and ASIC channels are involved in activating PHP at the mouse NMJ. We speculate that the partial blockade of nAChRs leads to a modest decrease in the pH of the synaptic cleft (∼0.2 pH units) and this activates ASIC channels on the presynaptic nerve terminal.